One-man demolition squad: Mohd Fairuz single handedly destroys Alor Setar All-Blues in rugby final - Noh, Dasheer (The Star, 2013)
NATIONAL fullback Mohd Fairuz Abdul Rahman was pronounced 'Man of the Match' in the Kedah-lmpressive Communications rugby final played at the SMK Tunku Abdul Rahman ground in Mergong, Alor Setar,Kedah.